Progress Being Made at Museum (Raton, NM Raton Range, 1977)
This article is about the grand opening of the Museum being postponed by the Raton Museum Board.
Newspaper Article
Master list item #: 76
File location is in the Raton file Cabinet
Keywords: Burch, Thomas (Tom) -- Curator; Rubin, Ron; Boggs, Jim; Stockton, Alvin -- Museum Board Chairman; Miles, Ron -- Palace Manager; Gurule, Bob; Raton Museum; A. R. F; New Mexico Museum; Museum Openings; Artifacts; Traveling Exhibits; Business Improvements; Fund Raising; Raton, New Mexico